Tinjauan Yuridis Budaya Hukum Dalam Penanggulangan Tindak PidanaPerjudian Sabung Ayam Dan Kartu Di Kabupaten Kebumen - Ferdian Pamungkas; Muhammad Yusril Irza (Wijayakusuma Law Review, 2024)
Gambling is dangerous for society, nation, and state, as well as very contradictive with religion, ethicsand morality. Several gambling forms have developed in daily life, many do it either openly orsecretly. Society considers that gambling is something ordinary, not violating the law, not be issued bylocal community, and even assumes that gambling is only a small violation. This research usesempirical normative research. The data sources that are used are primary and secondary data sourcesthat are obtained from primary, secondary, and tertiary legal materials. Primary data obtainingmethod is done by interview and secondary data obtaining method is done using related documents.The result of this research states that: (i) Society views that gambling is considered as ordinary actand becomes daily livelihood. Society views and values gambling as a recreation and accepts itsexistence, which they value it based only on its profit, without considering the negative impact. (ii)Coping of Cockfight Gambling and Card Gambling are using Economical, Legal, Social, and ReligiousApproach. People hold conference in order to give appeal/warning directly or indirectly.Keywords: Legal Culture, Gambling; Cockfighting, Playing Cards